2018
DOI: 10.1091/mbc.e18-06-0369
|View full text |Cite
|
Sign up to set email alerts
|

Essential requirement of mammalianPumiliofamily in embryonic development

Abstract: Mouse PUMILIO1 (PUM1) and PUMILIO2 (PUM2) belong to the PUF (Pumilio/FBF) family, a highly conserved RNA binding protein family whose homologues play critical roles in embryonic development and germ line stem cell maintenance in invertebrates. However, their roles in mammalian embryonic development and stem cell maintenance remained largely uncharacterized. Here we report an essential requirement of the Pum gene family in early embryonic development. A loss of both Pum1 and Pum2 genes led to gastrulation failu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 40 publications
3
27
0
Order By: Relevance
“…Pum1 −/− and Pum2 −/− mice were smaller throughout postnatal development, with a largely proportional size reduction among organs. A gene dosage effect of Pum alleles on body weight has been previously suggested ( Gennarino et al, 2015 ; Siemen et al, 2011 ), consistent with the overall dosage-sensitive behavior of PUM proteins ( Gennarino et al, 2018 ; Lee et al, 2016 ; Lin et al, 2018b ). In this study, we demonstrated a clear effect of gene dosage for Pum1 and, more interestingly, a synergistic effect of Pum1 and Pum2 on body and organ size.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Pum1 −/− and Pum2 −/− mice were smaller throughout postnatal development, with a largely proportional size reduction among organs. A gene dosage effect of Pum alleles on body weight has been previously suggested ( Gennarino et al, 2015 ; Siemen et al, 2011 ), consistent with the overall dosage-sensitive behavior of PUM proteins ( Gennarino et al, 2018 ; Lee et al, 2016 ; Lin et al, 2018b ). In this study, we demonstrated a clear effect of gene dosage for Pum1 and, more interestingly, a synergistic effect of Pum1 and Pum2 on body and organ size.…”
Section: Discussionsupporting
confidence: 84%
“…Given similar roles of Pum1 and Pum2 in cell proliferation, we therefore propose that Pum1 and Pum2 play a coordinated role in the control of body size. To test this hypothesis, we generated mouse mutants with different combinations of Pum1 - and Pum2 -null mutant alleles, with the exception of Pum1 −/− and Pum2 −/− double homozygotes, which failed during early embryonic development ( Lin et al, 2018b ). We noted a remarkable dosage effect of Pum genes on body weight ( Figures 7A and 7B ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pum1 has also been implicated in human neurodegeneration and motor ataxia (28,29) and in the maintenance of genomic stability in mice (30). Recent work showed that decreasing the number of Pum1 + and/ or Pum2 + alleles reduces body size in a dose-dependent manner, partly due to translational derepression of the cell-cycle inhibitor CDKN1B (26) and that complete deficiency of Pum1 and Pum2 leads to embryonic lethality (31). Conditional knockout of Pum1 and Pum2 in the nervous system affects neural stem-cell maintenance by derepressing the translation of many mRNAs (32,33).…”
Section: Significancementioning
confidence: 99%
“…Similarly, little is known about the function of Pum1; conditional knockout of Pum1 in the mouse testis results in decreased fertility (25). Recently, Pum1-Pum2 double mutant been shown to be embryonic lethal (26) and that Pum1 and Pum2 deficiencies reduces body size in a dose-dependent manner, partly due to translational de-repression of the cell cycle inhibitor CDKN1B (24).…”
Section: Introductionmentioning
confidence: 99%